Swamy's handbook 2023 : for central government staff - Muthuswamy; Brinda; Sanjeev (Chennai Swamy Publishers, 2023)
The book has been updated based on the seventh pay commission report and all latest orders conse4quent to acceptance.
Keywords: Handbook 2023.